Primary pancreatic lymphoma in a young adult male: a challenging diagnosis - Tupputi, Umberto; Testini, Valentina; Minerva, Nicola; Suriano, Claudia; Capuano, Michela; Guerra, Francesco Saverio; Mannatrizio, Domenico; Bellitti, Roberto; Scarabino, Tommaso; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2024)
Primary pancreatic lymphoma (PPL) is a rare clinical entity most likely to be misdiagnosed as pancreatic adenocarcinoma on presentation. The most common histological type of PPL is non-Hodgkin’s lymphoma. We present a case of a 48-year-old man admitted to our hospital for abdominal pain and progressive jaundice. A computed-tomography (CT) and magnetic resonance imaging (MRI) scan were performed and a large mass with slight enhancement after contrast agent administration at the pancreatic head was found. The patient underwent endoscopic-ultrasound (EUS) guided fine needle aspiration of the pancreatic mass. Histopathological diagnosis revealed a primary pancreatic lymphoma. We discuss the typical features of computed tomography (CT) and MRI of this rare clinical condition to help radiologists in the timely diagnosis for faster and more accurate diagnostic framing and to direct the patient to correct and timely treatment.